Alloy material for surfacing, surfacing method and mechanical part
By adopting a specific chemical composition of surfacing alloy material and layered surfacing technology, the problem of the surfacing alloy layer in the prior art cannot take into account wear resistance, few cracks, corrosion resistance and economicality, and achieve high wear resistance and corrosion resistance of the mixed parts, while reducing costs.
Patent Information
- Application Number
- CN202411935681.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
When forming the surfacing alloy layer, existing alloy materials for surfacing are unable to take into account wear resistance, few cracks, corrosion resistance and economy, which affects the life of mechanical parts such as dense mixers.
The chemical composition is C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, and the remaining amount is iron. Through the composition design of high-carbon silicon tungsten vanadium, combined with layered surfacing and tempering treatment, a surfacing alloy layer is formed that is wear-resistant, crack-free and corrosion-resistant.
It realizes high wear resistance, high strength and strong corrosion resistance of the components of the mixer, while reducing costs and reducing the generation and expansion of cracks during welding.
Smart Images

Figure CN119753500A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of surfacing welding, and in particular relates to an alloy material for surfacing welding, a surfacing welding method and a mechanical part. Background Art
[0002] The manufacturing process of rubber products usually includes the mixing chamber of the internal mixer, where the granular raw rubber is processed into condensed rubber through the stirring and extrusion of the rotor. In this process, all parts in contact with the rubber in the mixing chamber will go through a process from abrasive wear to adhesive wear. Since carbon black, quartz sand and metal oxides are added to the rubber during the refining process, the degree of wear and oxidation corrosion is further increased. Under the dual effects of wear and corrosion, the workpiece will quickly fail. In order to increase the service life of the workpiece, corrosion resistance is used as a solution. Internal mixer manufacturers basically use the method of adding a wear-resistant and corrosion-resistant layer on the surface of the workpiece, such as: surfacing hard alloy, electroplating hard chrome layer, etc., and the commonly used method is surfacing hard alloy layer, which is easy to operate and has high production efficiency.
[0003] The types of hard alloy for surfacing can be roughly divided into three categories: cobalt-based welding materials, nickel-based welding materials, and iron-based welding materials. The first two welding materials have good wear resistance, fewer cracks in the surfacing alloy layer, and good corrosion resistance. However, the cost of these two welding materials is very high, which is more than 5 to 10 times that of iron-based welding materials, and it is difficult to promote their use in large quantities. Currently, iron-based high-chromium cast iron and martensite-based Cr13 welding materials are still commonly used. The former material has excellent wear resistance, but its corrosion resistance is limited due to the presence of cracks. As tire technology advances, the latter material can no longer meet the wear requirements of some existing tire rubber compounds, and its service life has been reduced from more than 5 years to about 3 years.
[0004] The surface of the workpiece of the internal mixer is welded with a hard alloy layer to increase wear resistance and corrosion resistance. However, due to the curved surface of the workpiece of the internal mixer, cracks are easily generated during cooling when welding on the curved surface. When welding, cracks are easily generated when multiple layers are welded or when the welded part is welded again after cooling, which affects the wear resistance and strength improvement of the workpiece of the internal mixer. In addition, the alloy materials for surfacing welding add elements such as Mo, Co, Ni, and Nb, which are expensive and also affect the application of high-performance alloy materials for surfacing welding.
[0005] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the prior art that the surfacing alloy layer formed by the surfacing alloy material cannot take into account wear resistance, few cracks, corrosion resistance and economy, which affects the life of mechanical parts such as internal mixers, and to provide an alloy material for surfacing, a surfacing method and mechanical parts. The surfacing alloy layer formed by the surfacing alloy material has excellent wear resistance, few cracks, and excellent corrosion resistance. In particular, it is more suitable for curved surface welding such as internal mixers. The possibility of cracks caused by heat during multi-layer welding is reduced, and the cost is low.
[0007] In order to achieve the above-mentioned purpose, in a first aspect, the present invention provides an alloy material for surfacing, whose chemical composition is C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, and the balance is iron.
[0008] In some preferred embodiments, the chemical composition of the cladding alloy material satisfies 3.5%≤W+V≤6% in weight percentage.
[0009] In some preferred embodiments, the chemical composition of the cladding alloy material satisfies V / W of 0.7 to 0.9 in weight percentage.
[0010] In some preferred embodiments, the surfacing alloy layer formed by layered surfacing of the surfacing alloy material has a dispersed carbide hard phase, and the thermal expansion coefficient of the carbide hard phase is close to that of iron, thereby suppressing the stress generated between the substrate and the carbide hard phase.
[0011] Preferably, the carbide hard phase mainly includes tungsten carbide and vanadium carbide.
[0012] Preferably, the distribution density of the carbide hard phase is 1500 / mm 2 ~40000 / mm 2 , the equivalent circle diameter of the carbide hard phase is less than 1 μm.
[0013] In a second aspect, the present invention provides an alloy material for surfacing, whose chemical composition, in weight percentage, is C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, rare earth elements: 0.1-0.15, and the balance is iron.
[0014] In some preferred embodiments, the chemical composition of the cladding alloy material satisfies 3.5%≤W+V≤6% in weight percentage.
[0015] In some preferred embodiments, the chemical composition of the cladding alloy material satisfies V / W of 0.7 to 0.9 in weight percentage.
[0016] In some preferred embodiments, the surfacing alloy layer formed by layered surfacing of the surfacing alloy material has a dispersed carbide hard phase, and the thermal expansion coefficient of the carbide hard phase is close to that of iron, thereby suppressing the stress generated between the substrate and the carbide hard phase.
[0017] Preferably, the carbide hard phase mainly includes tungsten carbide and vanadium carbide.
[0018] Preferably, the distribution density of the carbide hard phase is 1500 / mm 2 ~40000 / mm 2 , the equivalent circle diameter of the carbide hard phase is less than 1 μm.
[0019] In a third aspect, the present invention provides a surfacing method, comprising: preheating a portion of a workpiece to be welded to 150°C to 250°C, performing layered surfacing using the surfacing alloy material described in the first aspect and / or the surfacing alloy material described in the second aspect, wherein the interlayer temperature of the layered surfacing is 200°C to 300°C, and performing a tempering treatment at a temperature of 540°C to 600°C after the layered surfacing.
[0020] In a fourth aspect, the present invention provides a mechanical part having a surfacing alloy layer on the surface of a base steel material, wherein the chemical composition of the surfacing alloy layer is, by weight percentage, C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, and the balance is iron;
[0021] Or, the chemical composition of the surfacing alloy layer is, by weight percentage, C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, rare earth elements: 0.1-0.15, and the balance is iron.
[0022] The invention adopts a high-carbon silicon-tungsten-vanadium composition design by matching C content of 0.7wt% to 1.4wt%, W content of 1.5wt% to 3.0wt%, V content of 1.5wt% to 3.0wt%, and Si content of 0.9wt% to 1.3wt%, and does not contain expensive elements such as Mo, Co, Ni, and Nb, thereby meeting the requirements of wear resistance, corrosion resistance, and less cracks for internal mixer parts, ensuring high hardness while improving wear resistance and reducing costs. In particular, under the premise of having high wear resistance, high strength, and strong corrosion resistance during long-term use, it is not easy to crack during long-term use, and is not easy to crack during welding, especially when multi-layer welding is performed at the curved surface of the internal mixer parts or when welding again after the welded part is cooled, the possibility of cracks caused by heat can be greatly reduced, and the welding performance of the welding material can be improved.
[0023] Specifically: high carbon is combined with high tungsten and high vanadium to provide a sufficient amount of tungsten carbide and vanadium carbide hard phases in a small dispersed distribution while refining the grains. During multiple welding, the carbides of W and V can be tempered at the welding temperature (200-300 degrees). During the tempering process, more tungsten carbide and vanadium carbide in a small dispersed distribution are precipitated, which can improve the hardness and wear resistance of the cladding alloy layer, and can inhibit the low-temperature tempering brittleness phenomenon, reduce the continuous precipitation of carbides between grains and the thermal expansion difference of adjacent grains to produce strong internal stress. Due to the thermal expansion coefficient of tungsten carbide and vanadium carbide, the hardness of the cladding alloy layer is improved. The thermal expansion coefficient is closer to that of iron, which reduces the possibility of stress between the matrix and the hard phase, thereby reducing the thermal impact of multiple heating on the weld during welding, especially during multiple welding, such as cracks, to achieve the suppression of crack generation and expansion, and improve the corrosion resistance of the surfacing alloy layer; the Cr content is 12wt% to 16wt%, which improves the hardness and wear resistance of the surfacing alloy layer; the high Si content, specifically the Si content is 0.9wt% to 1.3wt%, improves the tensile toughness of the surfacing alloy layer, avoids crack generation and expansion, and improves the corrosion resistance of the surfacing alloy layer. In the existing surfacing alloy materials, for example, Mo is used to improve the hardness and wear resistance of the surfacing alloy layer, and Ni is used to improve the corrosion resistance of the surfacing alloy layer, but the cost of adding the above elements to the welding material is high. The surfacing alloy material of the present invention, through the above synergistic effect, can still improve the hardness and wear resistance of the surfacing alloy layer, suppress the generation of cracks in the surfacing alloy layer, and improve the corrosion resistance of the surfacing alloy layer without adding high-priced elements such as Mo, Co, Ni, and Nb, and can greatly reduce the cost of the surfacing alloy material.
[0024] The alloy material for surfacing welding of the present invention contains rare earth, and the rare earth content is 0.1wt% to 0.15wt%, which can further promote grain refinement, so that the stress between grains generated by thermal expansion during welding is small and dispersed, avoiding stress concentration, and avoiding the continuous precipitation of carbides between grains and the thermal expansion difference between adjacent grains to produce strong internal stress, thereby further inhibiting the generation and expansion of cracks in the surfacing alloy layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is the first scanning electron microscope photograph of the surfacing alloy layer of Example 1.
[0027] Figure 2 This is the second scanning electron microscope photograph of the surfacing alloy layer of Example 1.
[0028] Figure 3 This is the first macroscopic photograph of the surfacing alloy layer of Example 5.
[0029] Figure 4 This is a second macroscopic photograph of the surfacing alloy layer of Example 5.
[0030] Figure 5 This is a macroscopic photograph of the surfacing alloy layer of Example 1.
[0031] Figure 6 This is a macroscopic photograph of the surfacing alloy layer of Example 4.
[0032] Figure 7 This is the first macroscopic photograph of the surfacing alloy layer of Comparative Example 1.
[0033] Figure 8 This is a second macroscopic photograph of the surfacing alloy layer of Comparative Example 1. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] The inventors of the present invention have found that in the prior art, the cladding alloy layer formed by the cladding alloy material cannot take into account the characteristics of wear resistance, less cracking, corrosion resistance and economy, which affects the life of mechanical parts such as internal mixers.
[0036] In this regard, in a first aspect, the present invention provides an alloy material for surfacing, whose chemical composition, in weight percentage, is C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, and the balance is iron.
[0037] The alloy material for surfacing welding of the present invention has a C content of 0.7wt% to 1.4wt%, a W content of 1.5wt% to 3.0wt%, and a V content of 1.5wt% to 3.0wt%.
[0038] W is an element that easily forms carbides. High W content is conducive to forming a large number of precipitated carbides with high carbon, which has a good effect on improving wear resistance. High C content and high W content can provide sufficient carbide hard phase, increase the wear-resistant phase content and thus improve wear resistance; however, W is easily dissolved in the γ phase in the austenite stage. When austenite is transformed into martensite, due to the high W content, W is prone to aggregation and precipitation in the form of flakes, thereby affecting wear resistance and easily generating cracks. Adding a higher V content can inhibit W aggregation and precipitation in the form of flakes, making tungsten carbide and carbide Vanadium is distributed in a micro-dispersed manner, thereby improving wear resistance. Tungsten carbide and vanadium carbide are distributed in a micro-dispersed manner in the martensite matrix, and are almost solid-dissolved in the martensite without diffusion and aggregation. In addition to improving wear resistance, continuous precipitation of carbides between grains can be reduced, thereby avoiding the strong internal stress generated by the continuous precipitation of carbides between grains and the thermal expansion difference of adjacent grains, thereby improving high-temperature endurance (little heat influence), reducing the thermal expansion coefficient, and making the thermal expansion of martensite small during welding, that is, the mutual pulling force between grains is small, thereby inhibiting the generation and expansion of cracks. The invention is used When the alloy material is used for layered cladding, when the next layer is welded, at the welding temperature, the previous welding layer will be affected by the heat in the interlayer temperature range, which is similar to the low-temperature tempering temperature. During the heat effect process, more tungsten carbide and vanadium carbide with tiny dispersed distribution can be precipitated. In particular, during the heat effect process, part of the residual austenite is converted into martensite, and the tungsten carbide and vanadium carbide in the martensite and residual austenite are more finely dispersed. On the basis of maintaining toughness and reducing crack generation, the more finely dispersed tungsten carbide and vanadium carbide also improve its wear resistance. Thus, the strength, wear resistance, corrosion resistance and crack reduction of the surfacing alloy layer can be improved, while low-temperature tempering is prone to low-temperature tempering brittleness, that is, when martensite decomposes, intermittent thin shell carbides are precipitated along the interface of martensite strips or sheets, thereby reducing the fracture strength of the grain boundary, and then making the grain boundary a path for crack expansion. The present invention has a W content of 1.5wt% to 3.0wt% and a V content of 1.5wt% to 3.0wt%, so that tungsten carbide and vanadium carbide are both slightly dispersed, and the low-temperature tempering brittleness phenomenon can also be suppressed, thereby controlling the generation and expansion of cracks. The smaller the grains, the smaller and more dispersed the mutual thermal expansion pulling force during welding is, and it is not easy to concentrate. The W content of the present invention is 1.5wt% to 3.0wt%, and the V content is 1.5wt% to 3.0wt%. It can also refine the grains, so that the stress between the grains generated by thermal expansion during welding is small and dispersed, avoiding stress concentration, reducing crack sensitivity, and controlling crack generation and expansion.The carbide hard phase of the present invention is mainly tungsten carbide and vanadium carbide, without molybdenum carbide, etc. During layered cladding, the welding point is heated multiple times, and the tungsten carbide, vanadium carbide and iron matrix expand due to the heat. Since the thermal expansion coefficients of tungsten carbide and vanadium carbide are close to those of iron, the stress between the matrix and tungsten carbide or vanadium carbide can be suppressed, and the possibility of forming a core for crack generation is reduced, which can further suppress the generation and expansion of cracks.
[0039] The Cr content of the alloy material for surfacing welding of the present invention is 12wt% to 16wt%. If the Cr element is lower than 12wt%, the hardness and wear resistance of the deposited metal will be reduced. If the Cr element exceeds 16wt%, the alloy has a tendency to austenitize, which will also cause the hardness of the surfacing alloy layer to decrease, affecting the wear resistance.
[0040] The Si content of the alloy material for surfacing welding of the present invention is 0.9wt% to 1.3wt%, which can improve the tensile toughness of the welding layer and avoid the generation and expansion of cracks. Since it does not contain elements such as Mo, Co, Ni, and Nb, the formation of iron silicon oxides can be controlled, and the problem of a substantial increase in iron silicon oxides and the generation and expansion of cracks due to a high Si content, specifically above 0.9wt%, will not occur.
[0041] The invention adopts a high-carbon silicon-tungsten-vanadium composition design by matching C content of 0.7wt% to 1.4wt%, W content of 1.5wt% to 3.0wt%, V content of 1.5wt% to 3.0wt%, and Si content of 0.9wt% to 1.3wt%, and does not contain expensive elements such as Mo, Co, Ni, and Nb, thereby meeting the requirements of wear resistance, corrosion resistance, and less cracks for internal mixer parts, ensuring high hardness while improving wear resistance and reducing costs. In particular, under the premise of having high wear resistance, high strength, and strong corrosion resistance during long-term use, it is not easy to crack during long-term use, and is not easy to crack during welding, especially when multi-layer welding is performed at the curved surface of the internal mixer parts or when welding again after the welded part is cooled, the possibility of cracks caused by heat can be greatly reduced, and the welding performance of the welding material can be improved.
[0042] Specifically: high carbon is combined with high tungsten and high vanadium to provide a sufficient amount of tungsten carbide and vanadium carbide hard phases in a micro-dispersed distribution while refining the grains. During multiple welding, the carbides of W and V can be tempered at the welding temperature (200-300 degrees). During the tempering process, more tungsten carbide and vanadium carbide in a micro-dispersed distribution are precipitated, which can improve the hardness and wear resistance of the cladding alloy layer, and can inhibit the low-temperature tempering brittleness phenomenon, reduce the continuous precipitation of carbides between grains and the thermal expansion difference of adjacent grains to produce strong internal stress. Due to the thermal expansion coefficient of tungsten carbide and vanadium carbide, the tungsten carbide and vanadium carbide are precipitated. The coefficient of thermal expansion of the Cr alloy is closer to that of iron, which reduces the possibility of stress between iron and inclusions, thereby reducing the thermal impact of multiple heating (such as cracks) on the weld during welding, especially during multiple welding processes, to achieve the suppression of crack generation and expansion, and improve the corrosion resistance of the surfacing alloy layer; the Cr content is 12wt% to 16wt%, which improves the hardness and wear resistance of the surfacing alloy layer; the high Si content, specifically the Si content is 0.9wt% to 1.3wt%, which improves the tensile toughness of the surfacing alloy layer, avoids crack generation and expansion, and improves the corrosion resistance of the surfacing alloy layer. In the existing surfacing alloy materials, for example, Mo is used to improve the hardness and wear resistance of the surfacing alloy layer, and Ni is used to improve the corrosion resistance of the surfacing alloy layer, but the cost of adding the above elements to the welding material is high. The surfacing alloy material of the present invention, through the above synergistic effect, can still improve the hardness and wear resistance of the surfacing alloy layer, suppress the generation of cracks in the surfacing alloy layer, and improve the corrosion resistance of the surfacing alloy layer without adding high-priced elements such as Mo, Co, Ni, and Nb, and can greatly reduce the cost of the surfacing alloy material.
[0043] The cemented carbide of the present invention does not contain elements such as Mo, Co, Ni, and Nb. Even if the C content is relatively high, higher than 0.7wt%, there will be no grain boundary segregation, and the thermal expansion at the grain boundary and between adjacent grains will be different, the grain boundary's ability to withstand tensile force will be reduced, and the problem of promoting crack generation and expansion will not occur. If the cemented carbide of the present invention contains elements such as Mo, Co, Ni, and Nb, it is easy to cause grain boundary segregation. During welding, the thermal expansion at the grain boundary and between adjacent grains is different, which promotes Fe and Si to form oxides. The Fe and Si oxides at the grain boundary and the grain boundary segregation phase cooperate to make the grain boundary's ability to withstand tensile force worse, thereby promoting crack generation and expansion. It is easy to precipitate W, V, Mo, Co, Ni, Nb and C at the grain boundary to form complex carbides, leading to crack expansion. The elements added by the present invention try to make tungsten carbide and vanadium carbide dispersed in the grains and precipitated, reducing the affinity of Ni and Co with impurity elements (P, Sb, Sn, Mn, As), promoting the segregation of impurity elements on the grain boundaries, and interacting with high carbon to easily produce large-sized carbides, resulting in increased risk of crack generation and other problems. Mo and carbon form molybdenum carbide inclusions with larger sizes, and the thermal expansion coefficient of molybdenum carbide is 1.5×10-6 / K, and the thermal expansion coefficient is greatly different from that of iron, resulting in a high risk of cracks, especially in the process of multiple welding, the risk of cracks caused by multiple heating of the weld increases. Not adding Mo can greatly reduce this risk. Nb is expensive and easily reacts with elements such as nitrogen. Not adding Nb can reduce costs and reduce the risk of cracks.
[0044] The surfacing alloy layer of the present invention has very few surface cracks and can be used as a transition layer hard alloy when manufacturing super wear-resistant parts. The surfacing alloy material of the present invention is preferably used in the form of a flux-cored wire.
[0045] In the present invention, the C content is, for example, 0.7wt%, 0.8wt%, 1.1wt%, 1.3wt% and 1.4wt%, the Si content is, for example, 0.9wt%, 1wt%, 1.1wt%, 1.2wt% and 1.3wt%, the Mn content is, for example, 1.5wt%, 1.7wt%, 1.9wt%, 2.2wt% and 2.3wt%, the Cr content is, for example, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, the W content is, for example, 1.5wt%, 1.7wt%, 1.9wt%, 2.1wt%, 2.3wt%, 2.6wt%, 2.7wt%, 2.9wt% and 3wt%, and the V content is, for example, 1.5wt%, 1.7wt%, 1.9wt%, 2.1wt%, 2.3wt%, 2.6wt%, 2.7wt%, 2.9wt% and 3wt%.
[0046] In some preferred embodiments, the chemical composition of the alloy material for surfacing satisfies 3.5%≤W+V≤6% in terms of weight percentage. Under this preferred scheme, it is more conducive to increasing the number of carbide hard phase particles formed and reducing the equivalent circular diameter of carbide hard phase particles, providing sufficient tungsten carbide and vanadium carbide hard phases in a micro-dispersed distribution in the surfacing alloy layer, refining the grains, improving the wear resistance of the surfacing alloy layer, avoiding the continuous precipitation of carbides between grains and the thermal expansion difference between adjacent grains to produce strong internal stress, inhibiting the generation and expansion of cracks, improving the corrosion resistance of the surfacing alloy layer, and reducing the cracks of the surfacing alloy layer without adding high-priced components such as Mo and Ni, ensuring the wear resistance and corrosion resistance of the surfacing alloy layer. The W+V content is, for example, 3.5%, 4%, 4.5%, 5%, 5.5% and 6%.
[0047] In some preferred embodiments, the chemical composition of the alloy material for surfacing is in weight percentage, and V / W is 0.7-0.9. W is more likely to form carbides, while V can inhibit W from aggregating and precipitating in the form of flakes when austenite is converted into martensite. At the same time, V can refine the grains, so that the stress between the grains generated by thermal expansion during welding is small and dispersed. Both V and W play a role in forming carbide hard phases, but each has a different and better role. Under this preferred scheme, by limiting V / W to 0.7-0.9, it is more conducive to forming dispersed and uniformly distributed tiny tungsten carbide and vanadium carbide hard phases in the surfacing alloy layer while refining the grains, thereby improving the wear resistance of the surfacing alloy layer, avoiding the continuous precipitation of carbides between grains and the thermal expansion difference of adjacent grains to produce strong internal stress, inhibiting the generation and expansion of cracks, improving the corrosion resistance of the surfacing alloy layer, and ensuring the performance of the surfacing alloy layer without adding high-priced components such as Mo and Ni. V / W is, for example, 0.75, 0.8, 0.85, and 0.9.
[0048] In some preferred embodiments, the surfacing alloy layer formed by layered surfacing of the surfacing alloy material has a dispersed carbide hard phase, and the thermal expansion coefficient of the carbide hard phase is close to that of iron, which suppresses the stress generated between the matrix and the carbide hard phase. Under this preferred solution, it is more conducive to improving wear resistance and reducing cracks.
[0049] Preferably, the carbide hard phase mainly includes tungsten carbide and vanadium carbide. Under this preferred solution, it is more conducive to improving wear resistance and reducing cracks.
[0050] Preferably, the surfacing alloy layer is dispersed with carbide hard phase, and the distribution density of the carbide hard phase is 1500 / mm 2 ~40000 / mm 2 , the equivalent circle diameter of the carbide hard phase is less than 1 μm. In this preferred embodiment, the distribution density of the carbide hard phase is not less than 1500 / mm 2 , which is more conducive to improving the wear resistance of the cladding alloy layer, and the distribution density is not more than 40000 / mm 2 , which is more conducive to reducing the crack sensitivity of the cladding alloy layer and inhibiting the generation and expansion of cracks. The equivalent circle diameter of the carbide hard phase is less than 1μm, which is more conducive to avoiding the continuous precipitation of carbides between grains and the thermal expansion difference between adjacent grains to produce strong internal stress, thereby inhibiting the generation and expansion of cracks. The distribution density of the carbide hard phase is further preferably 1500 / mm 2 ~35000 / mm 2 , and further preferably 2000 / mm 2 ~33000 / mm 2 , and further preferably 3000 / mm 2~30000 / mm 2 , and further preferably 5000 / mm 2 ~25000 / mm 2 , and further preferably 8000 / mm 2 ~22000 / mm 2 , and further preferably 10000 / mm 2 ~20000 / mm 2 The equivalent circle diameter of the carbide hard phase is further preferably less than 0.8 μm, and further preferably less than 0.5 μm.
[0051] In a second aspect, the present invention provides an alloy material for surfacing, whose chemical composition, in weight percentage, is C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, rare earth elements: 0.1-0.15, and the balance is iron.
[0052] The invention adopts a high-carbon silicon-tungsten-vanadium composition design by matching C content of 0.7wt% to 1.4wt%, W content of 1.5wt% to 3.0wt%, V content of 1.5wt% to 3.0wt%, and Si content of 0.9wt% to 1.3wt%, and does not contain expensive elements such as Mo, Co, Ni, and Nb, thereby meeting the requirements of wear resistance, corrosion resistance, and crack-freeness of internal mixer parts, ensuring high hardness while improving wear resistance and reducing costs. In particular, under the premise of having high wear resistance, high strength, and strong corrosion resistance during long-term use, it is not easy to crack during long-term use, and is not easy to crack during welding, especially when multi-layer welding is performed at the curved surface of the internal mixer parts or when welding again after the welded part is cooled, the possibility of cracks caused by heat can be greatly reduced, and the welding performance of the welding material can be improved.
[0053] Specifically: high carbon is combined with high tungsten and high vanadium to provide a sufficient amount of tungsten carbide and vanadium carbide hard phases with a small dispersed distribution while refining the grains. During multiple welding, the carbides of W and V can be tempered at the welding temperature (200-300 degrees). During the tempering process, more tungsten carbides and vanadium carbides with a small dispersed distribution are precipitated, which can improve the hardness and wear resistance of the surfacing alloy layer, and can inhibit the low-temperature tempering brittleness phenomenon, reduce the continuous precipitation of carbides between grains and the thermal expansion difference between adjacent grains to produce strong internal stress. Since the thermal expansion coefficients of tungsten carbide and vanadium carbide are closer to those of iron, the possibility of stress generation between iron and the hard phase is reduced, thereby reducing the thermal impact of multiple heating (such as cracks) on the weld during welding, especially multiple welding processes, thereby inhibiting the generation and expansion of cracks and improving the corrosion resistance of the surfacing alloy layer. In the existing surfacing alloy materials, for example, Mo is used to improve the hardness and wear resistance of the surfacing alloy layer, and Ni is used to improve the corrosion resistance of the surfacing alloy layer, but the cost of adding the above elements to the welding material is high. The surfacing alloy material of the present invention, through the above synergistic effect, can still improve the hardness and wear resistance of the surfacing alloy layer, inhibit the generation of cracks in the surfacing alloy layer, improve the corrosion resistance of the surfacing alloy layer, and can greatly reduce the cost of the surfacing alloy material.
[0054] The present invention further promotes grain refinement by having a rare earth content of 0.1wt% to 0.15wt%, so that the stress between grains generated by thermal expansion during welding is small and dispersed, thereby avoiding stress concentration and avoiding the strong internal stress generated by the continuous precipitation of carbides between grains and the thermal expansion difference of adjacent grains, thereby further inhibiting the generation and expansion of cracks in the surfacing alloy layer, further improving the dispersion effect of W and V, dispersion strengthening, and improving the wear resistance of the surfacing alloy layer; the hardness and wear resistance of the surfacing alloy layer are improved by having a Cr content of 12wt% to 16wt%; the tensile toughness of the surfacing alloy layer is improved by having a high Si content, specifically, the Si content is 0.9wt% to 1.3wt%, thereby avoiding the generation and expansion of cracks and improving the corrosion resistance of the surfacing alloy layer.
[0055] The C content of the present invention is, for example, 0.7wt%, 0.8wt%, 1.1wt%, 1.3wt% and 1.4wt%, the Si content is, for example, 0.9wt%, 1wt%, 1.1wt%, 1.2wt% and 1.3wt%, the Mn content is, for example, 1.5wt%, 1.7wt%, 1.9wt%, 2.2wt%, 2.3wt% and 2.5wt%, the Cr content is, for example, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, and the W content is, for example, 1.5 %, 1.7wt%, 1.9wt%, 2.1wt%, 2.3wt%, 2.6wt%, 2.7wt%, 2.9wt% and 3wt%, the V content is, for example, 1.5wt%, 1.7wt%, 1.9wt%, 2.1wt%, 2.3wt%, 2.6wt%, 2.7wt%, 2.9wt% and 3wt%, and the rare earth element content is, for example, 0.1wt%, 0.11wt%, 0.12wt%, 0.13wt%, 0.14wt% and 0.15wt%.
[0056] In some preferred embodiments, the chemical composition of the alloy material for surfacing is 3.5%≤W+V≤6% and / or V / W is 0.7-0.9 in weight percentage. Under this preferred scheme, 3.5%≤W+V≤6% is more conducive to providing sufficient tungsten carbide and vanadium carbide hard phases in the surfacing alloy layer in a dispersed manner, refining the grains, improving the wear resistance of the surfacing alloy layer, avoiding the continuous precipitation of carbides between grains and the thermal expansion difference between adjacent grains to produce strong internal stress, inhibiting the generation and expansion of cracks, and V / W is 0.7-0.9, which is more conducive to forming dispersed and uniformly distributed tiny tungsten carbide and vanadium carbide hard phases in the surfacing alloy layer while refining the grains, thereby improving the wear resistance of the surfacing alloy layer, inhibiting the generation and expansion of cracks, and improving the corrosion resistance of the surfacing alloy layer. The W+V content is, for example, 3.5%, 4%, 4.5%, 5%, 5.5% and 6%. V / W is, for example, 0.7, 0.75, 0.8, 0.85, and 0.9.
[0057] In some preferred embodiments, the surfacing alloy layer formed by layered surfacing of the surfacing alloy material has a dispersed carbide hard phase, and the thermal expansion coefficient of the carbide hard phase is close to that of iron, which suppresses the stress generated between the matrix and the carbide hard phase. Under this preferred solution, it is more conducive to improving wear resistance and reducing cracks.
[0058] Preferably, the carbide hard phase mainly includes tungsten carbide and vanadium carbide. Under this preferred solution, it is more conducive to improving wear resistance and reducing cracks.
[0059] Preferably, the surfacing alloy layer is dispersed with carbide hard phase, and the distribution density of the carbide hard phase is 1500 / mm2 ~40000 / mm 2 , the equivalent circle diameter of the carbide hard phase is less than 1 μm. In this preferred embodiment, the distribution density of the carbide hard phase is not less than 1500 / mm 2 , which is more conducive to improving the wear resistance of the cladding alloy layer, and the distribution density is not more than 40000 / mm 2 , which is more conducive to reducing the crack sensitivity of the cladding alloy layer and inhibiting the generation and expansion of cracks. The equivalent circle diameter of the carbide hard phase is less than 1μm, which is more conducive to avoiding the continuous precipitation of carbides between grains and the thermal expansion difference between adjacent grains to produce strong internal stress, thereby inhibiting the generation and expansion of cracks. The distribution density of the carbide hard phase is further preferably 1500 / mm 2 ~35000 / mm 2 , and further preferably 2000 / mm 2 ~33000 / mm 2 , and further preferably 3000 / mm 2 ~30000 / mm 2 , and further preferably 5000 / mm 2 ~25000 / mm 2 , and further preferably 8000 / mm 2 ~22000 / mm 2 , and further preferably 10000 / mm 2 ~20000 / mm 2 The equivalent circle diameter of the carbide hard phase is further preferably less than 0.8 μm, and further preferably less than 0.5 μm.
[0060] In a third aspect, the present invention provides a surfacing method, comprising: preheating a portion of a workpiece to be welded to 150°C to 250°C, performing layered surfacing using the surfacing alloy material described in the first aspect and / or the surfacing alloy material described in the second aspect, wherein the interlayer temperature of the layered surfacing is 200°C to 300°C, and performing a tempering treatment at a temperature of 540°C to 600°C after the layered surfacing.
[0061] According to the surfacing method of the present invention, before layered surfacing, the part to be welded of the workpiece is preheated to not less than 150°C, which is more conducive to reducing stress concentration and crack sensitivity, inhibiting crack generation, and not more than 250°C, which is more conducive to inhibiting austenitization, maintaining the hardness of the alloy layer stable, and increasing wear resistance; the interlayer temperature of layered surfacing is not less than 200°C and not more than 300°C, which is more conducive to effectively inhibiting crack generation; since the Cr content of the alloy material for surfacing is 12wt%-16wt%, and the V content is 1.5wt%-3.0wt%, after layered surfacing, a tempering treatment at 540°C-600°C is performed, which can significantly promote the secondary precipitation hardening of the carbide hard phase, and is more conducive to improving the hardness and wear resistance of the surfacing alloy layer.
[0062] The layered cladding of the present invention preferably adopts MIG welding (metal inert gas shielded welding), which can reduce spatter and is more conducive to surface forming.
[0063] In a fourth aspect, the present invention provides a mechanical part having a surfacing alloy layer on the surface of a base steel material, wherein the chemical composition of the surfacing alloy layer is, by weight percentage, C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, and the balance is iron;
[0064] Or, the chemical composition of the surfacing alloy layer is, by weight percentage, C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, rare earth elements: 0.1-0.15, and the balance is iron.
[0065] The surfacing alloy layer on the surface of the parent steel material of the present invention has a C content of 0.7wt% to 1.4wt%, a W content of 1.5wt% to 3.0wt%, a V content of 1.5wt% to 3.0wt%, a rare earth element content of 0.1wt% to 0.15wt%, a Si content of 0.9wt% to 1.3wt%, and a Cr content of 12wt% to 16wt%. Without adding high-priced elements such as Mo, Co, Ni, and Nb, the surfacing alloy layer has significantly improved hardness, wear resistance and corrosion resistance, and can significantly improve the life of mechanical parts.
[0066] The embodiments of the present invention are described in detail below, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0067] Example 1
[0068] The composition of the cladding alloy material is shown in Table 1, and the balance is iron. The cladding method comprises: preheating the to-be-welded portion of the workpiece to 200°C, performing layered cladding by MIG welding (molten inert gas shielded welding) process using the cladding alloy material of the above composition, maintaining the interlayer temperature of the layered cladding at 200°C to 300°C, and performing tempering after the layered cladding, maintaining the tempering temperature at 540°C to 600°C.
[0069] The metallographic test of the cladding alloy layer of Example 1 was carried out, and the distribution of the carbide hard phase was shown in Figure 1 and Figure 2 The hard phase of carbides is finely dispersed. The crack condition of the surfacing alloy layer of Example 1 was characterized. The characterization results are shown in Tables 2 and Figure 5 , which is a macroscopic photograph of a range of 200mm in length and 100mm in width.
[0070] The friction and wear tester of CSM brand was used to carry out friction and wear test on the surfacing alloy layer of Example 1. The test conditions were pre-calibrated, the temperature was 20°C, the pressure was 3N, the rotation speed was 60r / min, and the test time was 40min. The surface morphology of the surfacing alloy layer after the friction and wear test was observed by LEXTOLS5000 3D laser measuring microscope, and the volume reduction of the surfacing alloy layer was measured to obtain the wear resistance of the surfacing alloy layer. The results are shown in Table 2.
[0071] Embodiment 2-5
[0072] The methods of Example 1 were respectively followed, except that the composition of the alloy material for surfacing was different, as shown in Table 1. Corresponding tests were performed, and the test results are shown in Table 2. The macroscopic photograph of the surfacing alloy layer of Example 5 is shown in Figure 3 and Figure 4 , Figure 3 The macroscopic photograph of the surfacing alloy layer of Example 4 is shown in FIG. Figure 6 , which is a macroscopic photograph of a range of 200mm in length and 100mm in width.
[0073] Comparative Examples 1-5
[0074] The methods of Example 1 were respectively followed, except that the composition of the alloy material for surfacing was different, as shown in Table 1. Corresponding tests were performed, and the test results are shown in Table 2. The macroscopic photograph of the surfacing alloy layer of Comparative Example 1 is shown in Figure 7 and Figure 8 , Figure 7 This is a macro photo of a range of 200mm long and 100mm wide.
[0075] Table 1
[0076]
[0077] Table 2
[0078] Performance indicators crack Wear resistance Example 1 light good Example 2 light better Example 3 light better Example 4 Lighter better Example 5 Very light Excellent Comparative Example 1 Heavy Slightly worse Comparative Example 2 Very light Difference Comparative Example 3 Very light Difference Comparative Example 4 Heavy better Comparative Example 5 Heavy better
[0079] The wear resistance of the surfacing alloy layer is in the following order: excellent > good > better > slightly worse > poor. The wear resistance level of the surfacing alloy layer is obtained by calculating the volume of the surface layer of the surfacing alloy layer before friction (wherein the volume of the surface layer refers to the volume of the surfacing alloy layer within a certain distance from the surface of the surfacing alloy layer), and dividing the volume reduction by the volume of the surface layer of the surfacing alloy layer before friction to obtain the relative volume reduction. A relative volume reduction of ≤25% is called excellent, 25% < relative volume reduction ≤28% is called good, 28% < relative volume reduction ≤30% is called better, 30% < relative volume reduction ≤35% is called slightly worse, and a relative volume reduction greater than 35% is called poor.
[0080] The crack degree of the cladding alloy layer is as follows: extremely light > light > relatively light > heavy. The method for obtaining the crack degree level of the cladding alloy layer is to divide the cladding alloy layer on the surface of the to-be-welded part of the workpiece into grids of 200 mm in length and 100 mm in width, and to count the number of cracks and the average crack width in each grid. The crack degree of each grid is divided into cracks. The number of cracks is 0 to 2 and the average crack width is less than 0.15 mm, which is called extremely light. The number of cracks is 3 to 6 and the average crack width is less than 0.15 mm, which is called light. The number of cracks is 7 to 12 and the average crack width is less than 0.15 mm, which is called relatively light. The number of cracks is greater than 12 and / or the average crack width is greater than 0.15 mm, which is called heavy. The crack degree of the grid with the heaviest crack degree among a limited number of grids is used as the crack degree of the cladding alloy layer. The above method for obtaining the crack degree level is limited to when the length of the cracks on the surfacing alloy layer is less than 200 mm. When the surfacing alloy layer has cracks of more than 200 mm, the crack degree is called severe. The average crack width of the surfacing alloy layer of comparative examples 1, 4 and 5 of the present invention is greater than 0.3 mm.
[0081] Comparative Example 1 and Comparative Example 2, the chemical composition of the alloy material for surfacing welding is measured by weight percentage, and the V content is not less than 1.5, which can inhibit the generation of cracks and improve wear resistance; Comparative Example 2, the chemical composition of the alloy material for surfacing welding is measured by weight percentage, and the W content is not less than 1.5, which can improve wear resistance; Comparative Example 3, the C content is not less than 0.7, which can improve wear resistance; Comparative Example 4, the alloy material for surfacing welding does not contain Mo, Co, Ni, and Nb, which can inhibit the generation of cracks; Comparative Example 5, the Si content is 0.9wt% to 1.3wt%, which can inhibit the generation of cracks.
[0082] Comparing Example 5 with Example 1, the rare earth content is 0.1wt% to 0.15wt%, which is more conducive to suppressing the generation of cracks and improving wear resistance; comparing Example 1 with Example 2, the chemical composition of the alloy material for surfacing welding, measured in weight percentage, satisfies 3.5%≤W+V≤6%, which is more conducive to improving wear resistance; comparing Example 1 with Example 3, the chemical composition of the alloy material for surfacing welding, measured in weight percentage V / W is not greater than 0.9, which is more conducive to improving wear resistance; comparing Example 1 with Example 4, the chemical composition of the alloy material for surfacing welding, measured in weight percentage, V / W is not less than 0.7, which is more conducive to suppressing the generation of cracks and improving wear resistance.
[0083] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An alloy material for surfacing, characterized in that: Its chemical composition is calculated by weight percentage as follows: C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, and the balance is iron.
2. The alloy material for surfacing welding according to claim 1, characterized in that: The chemical composition of the alloy material for surfacing welding satisfies 3.5%≤W+V≤6% in weight percentage.
3. The alloy material for surfacing welding according to claim 1, characterized in that: The chemical composition of the alloy material for surfacing welding satisfies V / W of 0.7 to 0.9 in weight percentage.
4. The alloy material for surfacing welding according to claim 1, characterized in that: The surfacing alloy layer is formed by layered surfacing of the surfacing alloy material, and the surfacing alloy layer has a carbide hard phase dispersedly distributed.
5. The alloy material for surfacing welding according to claim 4, characterized in that: The carbide hard phase mainly includes tungsten carbide and vanadium carbide.
6. An alloy material for surfacing, characterized in that: Its chemical composition is calculated by weight percentage as follows: C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, rare earth elements: 0.1-0.15, and the balance is iron.
7. The alloy material for surfacing welding according to claim 6, characterized in that: The chemical composition of the alloy material for surfacing welding satisfies 3.5%≤W+V≤6% in weight percentage.
8. The alloy material for surfacing welding according to claim 6, characterized in that: The chemical composition of the alloy material for surfacing welding satisfies V / W of 0.7 to 0.9 in weight percentage.
9. The alloy material for surfacing welding according to claim 6, characterized in that: The surfacing alloy layer is formed by layered surfacing of the surfacing alloy material, and the surfacing alloy layer has a carbide hard phase dispersedly distributed.
10. The alloy material for surfacing welding according to claim 9, characterized in that: The carbide hard phase mainly includes tungsten carbide and vanadium carbide.
11. A surfacing method, characterized in that: include: The part to be welded of the workpiece is preheated to 150°C to 250°C, and layered surfacing is performed using the surfacing alloy material described in any one of claims 1 to 5 and / or the surfacing alloy material described in any one of claims 6 to 10, wherein the interlayer temperature of the layered surfacing is 200°C to 300°C, and after the layered surfacing, a tempering treatment at a temperature of 540°C to 600°C is performed.
12. A mechanical part having a cladding alloy layer on the surface of a base steel material, characterized in that: The chemical composition of the cladding alloy layer is C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, and the balance is iron; Or, the chemical composition of the surfacing alloy layer is, by weight percentage, C: 0.7-1.4, Si: 0.9-1.3, Mn: 1.5-2.5, Cr: 12-16, W: 1.5-3.0, V: 1.5-3.0, rare earth elements: 0.1-0.15, and the balance is iron.
Citation Information
Patent Citations
Submerged-arc welding overlaying repairing method for stainless steel hot rolled delivery roll
CN102189316A
Iron-based abrasion resisting and reducing surfacing flux-cored wire
CN102744532A
Heat treatment process for cutting teeth of surfacing coating of coal cutter
CN103921006A
Strengthening and toughening processing technology for welding deposit repairing of rolled steel
CN108311772A
Hot-strip mill roll
JP1999246950A